2014
DOI: 10.1007/s11136-014-0898-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between socioeconomic status and quality of life in older adults: a path analysis

Abstract: The path analysis indicated an indirect effect of SES on the quality of life by social functioning, depressive symptoms, and self-efficacy in community-dwelling older adults. Physical function did not have a direct effect on the quality of life. To improve the quality of life in older adults, additional focus is required on the socioeconomic psychosocial differences in the community-dwelling older population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 54 publications
3
41
1
1
Order By: Relevance
“…Socioeconomic status (SES) has been repeatedly reported to correlate with individual and/or community health outcomes including HRQoL (13). SES is a combined measure of an individual or family's economic and social position relative to others, based on 3 main predictors of educational level, income, and occupation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Socioeconomic status (SES) has been repeatedly reported to correlate with individual and/or community health outcomes including HRQoL (13). SES is a combined measure of an individual or family's economic and social position relative to others, based on 3 main predictors of educational level, income, and occupation.…”
Section: Introductionmentioning
confidence: 99%
“…SES is a combined measure of an individual or family's economic and social position relative to others, based on 3 main predictors of educational level, income, and occupation. It is commonly conceptualized as an individual or group's relative social standing or class on a hierarchy, based on various dimensions of sociology and economics (7,13). There is a list of key attributes of socio-economic status that contribute to the socio-economic differences between individuals and communities (13,14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 In two community-dwelling studies, depression level were associated with poorer quality of life. 23,24 Depression symptoms, according to RDC/TMD, are prevalent in this group; disagreeing with another study that showed a prevalence of 6.3% of people with depression, anxiety and emotional problems; however, that percentage included young adults, not only elderly population. 5 On the other hand, one study has shown that depression was present in 100% of the institutionalized elderly, among which 96% were serious or severely depressed.…”
Section: Discussionmentioning
confidence: 63%
“…Sosyo-demografik özelliklere ilişkin bu sonuçlar Türkiye geneli istatistiklerle, [20,[35][36] Türkiye'de sağlıklı yaşam tarzı davranışlarına yöne-lik yaşlılar üzerine yapılan çalışmalarla [22][23][24][25]30] ve diğer ülkelerde yapılan çalışmalarla [8,[13][14][15][16][18][19] Daha önce yapılan çok sayıda kesitsel ve kohort çalışmada sosyo-ekonomik faktörlerin yaşlı yaşam kalitesi üzerine etkisi kanıtlanmıştır. [39][40][41][42] Bu çalışmanın temel konusu olan sağlıklı yaşam tarzı alışkanlıkları açısından yaşam kalitesi değer-lendirildiğinde; yeterli meyve-sebze tüketiminin yaşlı sağlığı ve yaşam kalitesini olumlu etkilediğini gösteren çalışmalar mevcuttur. [43][44][45][46] Türkiye'de ve dünyanın farklı ülkelerinde yapılan çok sayıda araştırmada da yaşlı bireylerde fiziksel hareketliliğin yaşam kalitesi üzerine olumlu etkisi kanıtlanmıştır.…”
Section: Sağlıklı Yaşam Tarzı Alışkanlıklarıunclassified